How Can Social Media Get Us in Trouble? - Langenfeld, Sean J.; Batra, Rishi (Clinics in Colon and Rectal Surgery, 2017)
When utilized properly, social media offers several personal and professional benefits for the practicing surgeon, including peer networking, education, e-mentorship, marketing, recruitment, and patient outreach. However, unprofessional online behavior is common among surgeons, and this improper use of social media can be quite dangerous. This article reviews the dangers of social media and illustrates this with examples of unprofessional behavior and the associated consequences. It also provides recommendations for maintaining a professional and productive online persona. Surgeons must understand the various social media platforms and their target audience while upholding online professionalism at all times.
Keywords: professionalism; social media; disciplinary action; Facebook; Twitter; Instagram